FAKTOR YANG MEMPENGARUHI VARISES VENA TUNGKAI BAWAH (VVTB) PADA GURU SEKOLAH DASAR (SD) DI DESA SECURAI SELATAN KECAMATAN BABALAN KABUPATEN LANGKAT TAHUN 2019 - Riyan Sabputra; Santy Deasy Siregar; Rapael Ginting (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2019)
Varicose veins of the lower limb (VVTB) abnormalities of blood vessels in the lower extremities. The prevalence of VVTB in Europe is around 50% of the adult population. The incidence of varicose veins in Indonesia is 25% to 30% in women and 10% to 20% in men. Based on a preliminary survey in Desa Securai Selatan, Babalan Subdistrict, Langkat Regency, out of 10 people there were 7 people suffering from VVTB. Therefore, the authors want to find out the factors that affect Varicose Veins of Lower Legs (VVTB) in Primary School (SD) teachers in Securai Selatan Village, Babalan Subdistrict, Langkat Regency in 2019. Types of analytical research with cross sectional approach. The population is Elementary School (SD) teachers in Securai Selatan Village, Babalan Subdistrict, Langkat Regency as many as 35 female teachers consisting of SD Alur Rejo having 19 teachers, SD Batang Rejo having 6 teachers and SD Sendayan having 10 teachers. The sample in this study using total sampling. Data analysis was performed with univariate and bivariate analysis with chi-square test. The results of the study were elementary school teachers based on the long standing majority of the categories that did not last long, namely 19 people (54.3%), the majority age category â‰¥ 30 years was 28 people ( 80.0%), majority education in S1 category is 33 people (94.3%), obesity in the majority category is not obese that is 18 people (51.4%), the use of high heels majority of the categories do not wear high heels that is 25 people (71 , 4%), the majority of VVTB categories were not VVTB, namely 28 people (80.0%). The conclusion is the influence of long standing factors, age, obesity and the use of high heels on VVTB in elementary school teachers in Securai Selatan Village, Babalan Subdistrict, Langkat Regency in 2019. The research suggestion is that teachers are expected to prevent VVTB by minimizing the work of teachers who are dominated by standing length of time in teaching and limiting the use of high heels to less than or equal to 5 cm because the use of shoes more than 5 cm is easier for potential varicose veins in the lower limbs